’Helen of Troy’ of the Middle East – Syria Seen through the Theories of International Relations - Vasileva, Evgenia (Research Papers, 2018)
The main objective of the article is to present an analytical reflection on a scientific conversation, carried out in the form of a conference. The article is organized around two different dimensions.One dimension is formed by the themes and main positions of the given speeches.Another dimension is shaped by the exact theoretical approaches for research on international relations, to which the themes and positions may be addressed, and assessing the explanatory power of the theories. TheDefensive realism gives a possible explanation of why the "situation" in Syria continues for so long. TheOffensive realism provides insight about understanding the high levels of escalation in Syria. The positions betweenDefensive realism and liberalism overlap on the role of small actors and the potential advantages of defense. Thesystem approach complicates the analysis and helps to describe in detail and schematically predict. Theneoliberal position is close to the Defensive realism that in Syria the EU is the biggest loser.Finally, while we make a trial to predict what will happen in Syria, to have knowledge is important due to the existence of many manipulations. However, both (knowledge and manipulation) aresocially constructed and obey the principle of repetition like in the words "and so on", in other words, the human history will repeat, change and continue.